1992
DOI: 10.1002/mus.880150416
|View full text |Cite
|
Sign up to set email alerts
|

Role of autonomic nerve functions in patients with familial amyloidotic polyneuropathy as analyzed by laser doppler flowmetry, capsule hydrograph, and cardiographic R–R interval

Abstract: Laser Doppler flowmetry (LDF) was conducted on familial amyloidotic polyneuropathy (FAP) patients and asymptomatic carriers of FAP. Vasoconstrictive responses in the 11 FAP patients tested, induced by deep inspiration, were markedly depressed compared with those of the healthy controls. The responses decreased with the progression of FAP, with no responses being elicited from the 7 patients in stages 2 (moderate) to 4 (terminal). Interestingly, vasoconstrictive responses following deep inspiration also were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 10 publications
(4 reference statements)
1
34
1
1
Order By: Relevance
“…17,20,64 Circulatory complications during liver transplantation are reported in several series 54,[65][66][67] and are more common in patients with FAP than in patients who undergo transplantation for liver disease. 68 Intraoperative and postoperative hypotension are serious problems that do not appear related to amyloid deposits in the heart or conduction abnormalities.…”
Section: Autonomic Polyneuropathymentioning
confidence: 99%
See 1 more Smart Citation
“…17,20,64 Circulatory complications during liver transplantation are reported in several series 54,[65][66][67] and are more common in patients with FAP than in patients who undergo transplantation for liver disease. 68 Intraoperative and postoperative hypotension are serious problems that do not appear related to amyloid deposits in the heart or conduction abnormalities.…”
Section: Autonomic Polyneuropathymentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] Autonomic nervous system dysfunction is often present early during the course of the disease, causing severe orthostatic hypotension and impotence. 6,[16][17][18][19][20][21] In the final stage of the disease, the patients are severely incapacitated, bedridden or bound to a wheelchair, malnourished, and have urinary and fecal incontinence. [6][7][8] Symptoms from the eye are common, and amyloid deposits in the corpus vitrium may lead to blindness if left untreated.…”
mentioning
confidence: 99%
“…1). A recent study of peripheral autonomic dysfunction by laser Doppler flowmetry revealed that autonomic nerves are first impaired in FAP patients (8).…”
Section: Clinical Features and Genetics Of Fapmentioning
confidence: 99%
“…The disease is characterized by a progressive peripheral and autonomic polyneuropathy [2][3][4]. The patients are in the later stages of the disease severely incapacitated, bedridden or in a wheelchair.…”
Section: Introductionmentioning
confidence: 99%
“…Autonomic nervous dysfunction is found in FAP patients early after onset of the disease [3,4] Autonomic disturbances disrupt blood pressure regulation, which sometimes leads to fatal complications during liver transplantation for FAP [5]. Severe malnutrition develops subsequently in all FAP patients, and the development of malnutrition may be linked to autonomic dysfunction [6].…”
Section: Introductionmentioning
confidence: 99%